Grading of Neuroendocrine Carcinomas: Correlation of 68Ga-PET/CT Scan with Tissue Biomarkers. (2nd December 2018) - Liverani, Chiara; Bongiovanni, Alberto; Mercatali, Laura; Foca, Flavia; Pieri, Federica; De Vita, Alessandro; Spadazzi, Chiara; Miserocchi, Giacomo; Recine, Federica; Riva, Nada; Nicolini, Silvia; Severi, Stefano; et al.
Abstract : There is a growing need for more accurate biomarkers to facilitate the diagnosis and prognosis of patients with grade (G) 3 neuroendocrine carcinomas (NECs). In particular, the discrimination between well-differentiated neuroendocrine carcinomas (WD-NECs) and poorly differentiated neuroendocrine carcinomas (PD-NECs) is still an unmet need. We previously showed that 68 Gallium-( 68 Ga-) PET/CT positivity is a prognostic factor in patients with gastroenteropancreatic (GEP) G3 NECs, correlating with a better outcome in terms of overall survival. Here, we hypothesize that 68 Ga-PET/CT could help to discriminate between WD-NECs and PD-NECs, adding complementary information to that obtained from morphologic and biologic factors. A retrospective, single-institution study was performed on 11 patients with histologically confirmed, measurable G3 large- or small-cell GEP-NECs according to the 2017 WHO classification. The staging procedures included a 68 Ga-PET/CT scan. Results of 68 Ga-PET/CT were correlated in univariate analysis with loss of tissue immunohistochemical expression of DAXX/ATRX or RB1 frequently associated with WD-NECs or PD-NECs, respectively. None of the patients with positive 68 Ga-PET/CT showed loss of RB1 expression, whereas among those (n = 6 ) with negative 68 Ga-PET/CT, 4 showed loss of expression. A trend towards a correlation between loss of RB1 expression and negative 68 Ga-PET/CT was observed. Our preliminary data support the hypothesis that PD-NECs carrying RB1 mutation and loss of its expression may be associated with negative 68 Ga-PET/CT. If confirmed in a larger clinical trial, 68 Ga-PET/CT would help in the stratification of G3 NECs.